ANALYSIS OF STYLISTIC TRANSFORMATIONS IN WILKIE COLLINS' THE WOMAN IN WHITE - Inog‘omjonova Robiya Rustamjon qizi (Western European Studies, 2024)
This article is devoted to wilkie Collins' analysis of stylistic transformations in The Woman in White. The stylistic structures used in the poem, their uniqueness, and these stylistic changes are analyzed from a linguistic point of view. It also describes the author of The Woman in White, the history of the work, and the opinions of a number of renowned scholars
Keywords: relia; metaphor; metonics; blessing